2022
DOI: 10.3390/ijerph191912449
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Different Anthropometric Indices to Assess the Body Composition of Young Women in Relation to the Incidence of Obesity, Sarcopenia and the Premature Mortality Risk

Abstract: The objective of the study was to evaluate the stratification of young women based on the assessment of body composition according to several currently recommended anthropometric indices and parameters, as well as the presence of obesity, sarcopenic obesity and the risk of premature death. Three hundred and three young Caucasian women aged 18–25 years were included in the cross-sectional observational study. For the purposes of the study, we used the bioelectrical impedance method and applied the obtained data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
1
3
0
1
Order By: Relevance
“…Our previous studies [24,29,51] confirmed that body composition analysis should be the basis for assessing obesity risk. In the present study, we found that women with obesity had a higher body composition parameter PBF compared to women with overweight (44.86 ± 4.31% and 38.74 ± 2.83%, respectively, p < 0.001).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Our previous studies [24,29,51] confirmed that body composition analysis should be the basis for assessing obesity risk. In the present study, we found that women with obesity had a higher body composition parameter PBF compared to women with overweight (44.86 ± 4.31% and 38.74 ± 2.83%, respectively, p < 0.001).…”
Section: Discussionsupporting
confidence: 55%
“…Systolic and diastolic blood pressures (mm Hg) were measured in duplicate using the digital upper arm electronic monitor (Omron M7 Intelli IT, HEM-7361T-EBK, Omron Healthcare Co., Ltd., Tokyo, Japan). Participants were instructed to maintain a seated and calm posture, ensuring they had rested for a minimum of 15 min prior to each measurement [29,40]. All anthropometric characteristics were recorded as the average values.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Также стратификация мужчин по ИМТ позволила установить значимую динамику возрастания анализируемых переменных по мере увеличения значений ИМТ в каждой возрастной группе. Более высокие значения мышечного компонента в группе лиц с наличием избыточной массы тела и ожирением сопоставимы с результатами других авторов, которые объясняют данный факт анаболической активностью из-за нагрузки избыточной массы тела на опорно-двигательный аппарат [24]. Необходимо указать, что в возрастном аспекте нами было отмечено изменение диапазонов размаха ИМТ от минимального к максимальному значению: так, в группе юношей размах ИМТ составил 16,15-36,33 кг/м 2 , у представителей 1-го зрелого возраста -16,36-41,4 кг/м 2 , в выборке 2-го зрелого возраста -19,02-48,52 кг/м 2 со значительным смещением нижнего порога у мужчин пожилого возраста с 25,03 кг/м 2 при максимальном пороге, равном 49,69 кг/м 2 .…”
Section: т а б л и ц аunclassified
“…Therefore, central obesity represented by waist circumference (WC) and waist-hip ratio (WHR) should also be considered, which is more related to mortality (20)(21)(22). Compared with WHR, WC could be a better tool in practice for its significant correlation with visceral fat and fewer anthropometric measurement requirements (23)(24)(25). Furthermore, WHO also suggests that although BMI and abdominal adiposity measures may be highly correlated, considering the utility of joint use of the two indicators is desirable (26).…”
Section: Introductionmentioning
confidence: 99%